Serbia and Montenegro : Second Review Under the Extended Arrangement and Requests for Waiver and Modification of Performance Criteria, and for Extension of Repurchase Expectations. (IMF Staff Country Reports; Country Report ;, 2003)
Economic performance in 2002 was generally favorable with good policy implementation, but considerable risks remain. Structural reforms have fallen behind program expectations, but the delays are being addressed. The discussions highlighted the need for prudent policies and strengthening of structural reforms. The structural reforms will focus on tax administration and expenditure management, banking supervision and resolution, and privatization. Monetary and exchange rate policies in Serbia should continue to balance the inflation and external objectives. Serbia and Montenegro's performance under the Extended Arrangement has remained good.